Drivers of growth in fast emerging economies: A dynamic instrumental quantile approach to real output and its rates of growth in BRICS and MINT countries, 2001-2011 - Simplice Asongu; Nicholas M. Odhiambo (African Governance and Development Institute (AGDI), 2018)
We analyze the evolution of fast emerging economies of the BRICS (Brazil, Russia, India, China & South Africa) and MINT (Mexico, Indonesia, Nigeria & Turkey) countries, by assessing growth determinants throughout the conditional distributions of the growth rate and real GDP output for the period 2001-2011. An instrumenal variable (IV) quantile regression approach is complemented with Two-Stage-Least Squares and IV Least Absolute Deviations. We find that the highest rates of growth of real GDP per head, among the nine countries of this study, corresponded to China, India, Nigeria, Indonesia and Turkey, but the highest increases in real GDP per capita corresponded, in descending order, to Turkey China, Brazil, South Africa and India. This study analyzes the impacts of several indicators on the increase of the rate of growth of real GDP and on the logarithm of the real GDP. We analyze several limitations of the methodology, related with the selection of the explained and the explanatory variables, the effect of missing variables, and the particular problems of some indicators. Our results show that Net Foreign Direct Investment, Natural Resources, and Political Stability have a positive and significant impact on the rate of growth of real GDP or on real GDP.
Keywords: C52; F21; F23; O40; O50; 330; Economic Growth; Emerging countries; Quantile regression